BACK TO THE FUTURE: A LESSON IN FAIRNESS AND RETROSPECTIVITY S v Acting Regional Magistrate, Boksburg: Venter and Another (CCT 109/10) [2011] ZACC 22; 2011 (2) SACR 274 (CC) - Suhayfa Bhamjee (Obiter, 2021)
The purpose of any legislation is to safeguard the welfare of society. Any law that fails to do that cannot justify its existence. In S v Acting Regional Magistrate, Boksburg: Venter ((CCT 109/10) [2011] ZACC 22; 2011 (2) SACR 274 (CC)) the question of nullity of the particular wording of section 69 of the Criminal Law (Sexual Offences and Related Matters) Amendment Act (32 of 2007, hereinafter “the Act”) and its subsequent constitutionality, were in question. The court had to decide whether to confirm the ruling of the SouthGauteng High Court, Johannesburg (Case No A11/2010) that the particular wording of the section was inconsistent with the Constitution of the Republic of South Africa, 1996, or whether it could apply the various rules of interpretation and save the section from invalidity.